Framework for Continuous Assessment and Improvement of Occupational Health and Safety Issues in Construction Companies - Shahram Mahmoudi; Fakhradin Ghasemi; Iraj Mohammadfam; Esmaeil Soleimani (Elsevier, 2014)
Background: Construction industry is among the most hazardous industries, and needs a comprehensive and simple-to-administer tool to continuously assess and promote its health and safety performance. Methods: Through the study of various standard systems (mainly Health, Safety, and Environment Management System; Occupational Health and Safety Assessment Series 180001; and British Standard, occupational health and safety management systems-Guide 8800), seven main elements were determined for the desired framework, and then, by reviewing literature, factors affecting these main elements were determined. The relative importance of each element and its related factors was calculated at organizational and project levels. The provided framework was then implemented in three construction companies, and results were compared together. Results: The results of the study show that the relative importance of the main elements and their related factors differ between organizational and project levels: leadership and commitment are the most important elements at the organization level, whereas risk assessment and management are most important at the project level. Conclusion: The present study demonstrated that the framework is easy to administer, and by interpreting the results, the main factors leading to the present condition of companies can be determined.